Application of Interactive Psychological Exercises for Psychological Rehabilitation of Combatants - Perelygina, Lina; Balabanova, Liubov; Ovsiannikova, Yanina; Pokhilko, Diana; Kerdyvar, Valentyn (Journal of Education Culture and Society, 2024)
Aim. Military operations in Ukraine have caused signs of mental trauma in the combatants. Such individuals need active psychological rehabilitation involving effective methods. One of them is the use of interactive psychological simulators that help to rethink one’s perception of reality and oneself in it, learn new types of behaviour. The aim is to identify the effectiveness of using interactive psychological simulators in improving the psycho-emotional state of combatants.Methods. The following methods were employed during the diagnostics: Diagnosis of Psychological Safety of a Person (DPSP-88), Lemur-Tessier-Fillion Psychological Stress Measure (PSM25), Beck’s Depression Inventory (BDI), Taylor Manifest Anxiety Scale (TMAS). Descriptive statistics and Student’s t-test were applied for statistical processing.Results. The study proved that the use of an interactive psychological simulator by combatants increased their Psychological Safety Index (t = 8.42; p≤0.001), reduced stress (t = 4.39; p≤0.001), depression (t = 5, 14; p≤0.001), and anxiety (t = 5.43; p≤0.001). This makes it possible to expand the range of psychological rehabilitation of combatants through the introduction of psychological simulators.Conclusion. The obtained results are important for psychologists and rehabilitators, as they prove the effectiveness of the use of psychological simulators in the psychological rehabilitation of combatants. This can improve the process of psychological recovery of the military, contribute to their social and psychological adaptation, resocialisation. Based on the obtained results, it is planned to expand the possibilities of using psychological simulators in the rehabilitation of combatants. Their introduction into the mandatory system of providing assistance to victims of hostilities will reduce the time of their psychological recovery.